Mechanistic insight into the electron-donation effect of modified ZIF-8 on Ru for CO2 hydrogenation to formic acid. (June 2022) - Hu, Xiaowei; Luo, Maowei; ur Rehman, Mooeez; Sun, Junhao; Yaseen, Hamzah A.S.M.; Irshad, Faisal; Zhao, Yujun; Wang, Shengping; Ma, Xinbin
Abstract: The electron-donating effect of supports on active metals has been reported to be beneficial to improve catalytic activity of heterogenized molecule catalysts for CO2 hydrogenation to formic acid. However, this effect has not been discussed in depth from the perspective of reaction mechanism, especially for CO2 activation with the combination of theoretical calculations. Herein, we report a catalyst prepared via anchoring RuCl3 on a post-synthetic modified (PSM) zeolitic imidazolate framework-8 (ZIF-8) in which linkers 3-methyl-1, 2, 4-triazole (Mtz) with a surplus of uncoordinated N sites have been incorporated. X-ray photoelectron spectroscopy (XPS) and density functional theory (DFT) calculations reveal that uncoordinated N sites in linkers donate additional electron-density to Ru, resulting in the decrease of energy barrier of CO2 activation. And the RuCl3 @ZIF-8-Mtz(0.29) catalyst containing the most Mtz ligands displayed the highest catalytic performance for the CO2 hydrogenation to formic acid as compared to RuCl3 @ZIF-8-Mtz(0.15) and RuCl3 @ZIF-8. Graphical Abstract: ga1 Highlights: DFT calculations and experiments demonstrated N-sites in Mtz donated additional electron-density to Ru. CO2 was easier to be activated on Mtz-Ru than Mim-Ru due to the improved electron-density around Ru species. RuCl3 @ZIF-8-Mtz(0.29) containing most Mtz exhibited the best catalytic activity for CO2 hydrogenation.